Answers

2014-11-22T14:46:48+05:30
given --->x-2=0        ===>  x=2
               now put the above value in given equation........ 
  p{x}=     2x³-2x+k=0
 p{2}=      2[2]³-2[2]+k=0
           =>  2[8]-4=-k
           =>  16-4=-k
          =>    12=-k
             so,                                    k=-12
                                                                                                      plz mark it best
1 5 1
2014-11-22T18:42:23+05:30
Given that x-2 is factor of 2x^3-2x+k
That means when divide 2x^3-2x+k by x-2 we will get the zero in remainder
Therefore x-2=0
                x=2
Substitue x=2 in 2x^3-2x+k=0
2(2)^3-2(2)+k=0
16-4+k=0
12+k=0
k=-12
Therfore k=-12
0